High‐Sensitivity Cardiac Troponin I for Risk Stratification in Older Adults. Issue 4 (4th November 2020) - Tang, Olive; Matsushita, Kunihiro; Coresh, Josef; Hoogeveen, Ron C.; Windham, B. Gwen; Ballantyne, Christie M.; Selvin, Elizabeth
Abstract : BACKGROUND/OBJECTIVES: Traditional cardiovascular risk factors are less predictive in older age. High‐sensitivity cardiac troponin I (hs‐cTnI) is a marker of subclinical cardiomyocyte damage associated with cardiovascular risk in middle‐aged adults. We hypothesized hs‐cTnI would be indicative of mortality and cardiovascular risk beyond traditional cardiovascular risk factors in older adults and may be more discriminatory compared to hs‐troponin T (hs‐cTnT). DESIGN: Prospective cohort study. SETTING: Population‐based Atherosclerosis Risk in Communities (ARIC) Study. PARTICIPANTS: We included 5, 876 ARIC participants at Visit 5 (2011–2013). OUTCOMES AND MEASURES: We used Cox regression for the association of hs‐cTnI categories (women: <4, 4–<10, ≥10 ng/ml; men: <6, 6–<12, ≥12 ng/ml, prevalent cardiovascular disease (CVD)) with mortality and incident CVD (atherosclerotic CVD [ASCVD]: coronary heart disease or stroke, or heart failure). RESULTS: Participants were ages 66 to 90, 23% black, 42% male, and 24% had prevalent CVD. There were 1, 053 (321 CVD) deaths (median follow‐up 6.3 years). Participants with elevated hs‐cTnI and no CVD (7% of participants) had mortality risk similar to those with a history of CVD (55.6 vs 55.7 deaths/1, 000 person‐years, P = .99). After adjustment, elevated hs‐cTnI and no CVD (hazard ratio (HR) = 2.38, 95% confidence interval (CI) = 1.85–3.06) and prevalent CVD (HR = 2.21, 95% CI = 1.90–2.57) remained associated with mortality, compared to low hs‐cTnI and no CVD. Elevated hs‐cTnI was independently associated with incident CVD (HR = 3.41, 95% CI = 2.58–4.51), ASCVD (HR = 2.02, 95% CI = 1.36–2.98), and heart failure (HR = 6.16, 95% CI = 4.24–8.95). The addition of hs‐cTnI significantly improved C‐statistics for all outcomes and added greater discrimination than hs‐cTnT for cardiovascular mortality and incident heart failure. CONCLUSIONS: Hs‐cTnI improves mortality and CVD risk stratification in older adults beyond traditional risk factors and improved model discrimination more than hs‐cTnT for certain outcomes. Elevated hs‐cTnI without CVD identifies a high‐risk group with comparable mortality risk as those with a history of clinical CVD.